Cost Estimation of the Models Using Harmony Search - T. Vijaya Saradhi, Dr; Lakshmi Pravallika, A; Manoj, M (International Journal of Engineering and Technology, 2018)
To estimate the cost of model accurately on which the software is functioning is one of the most important things in the software project. But due to the varying nature of the software, and complexity, accurate cost estimation of software has become difficult. Ascertaining the cost of the software at the beginning stage is helpful for designing the other activities of software development. Former estimation of the needed exertion to Creating programming need benefited the advancement acknowledging those provision about Meta heuristic streamlining calculations. These calculations need aid possibility and might a chance to be connected Likewise functional devices for programming expense estimation. In the recent times Meta- heuristic algorithms with high accuracy have brought a great improvement in the field of the software engineering. In this paper we have discussed about the one of the algorithm which help in software cost estimation which is Harmony Search. Â Â